Hvad en lille brun pakke gemte. En studie i dronning Louises programsamling - Røllum-Larsen, Claus (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2015)
In 1954, along with Queen Louise’s (1817–1898) collection of music, The Royal Library also received a small collection of programmes, mainly of private arrangements within the royal court. A small number of programmes of private dramatic performances are particularly interesting. They show that the queen was present at such arrangements, and that she herself took part when young. A series of programmes also documents Queen Louise’s presence at i.a. the wedding of her grandchild, the Crown Prince Konstantin, in Athens in 1889.